A review of Caenohalictus species from southern Brazil (Apoidea, Caenohalictini) - Cappola, Victor; Gonçalves, Rodrigo B. (Zootaxa, 2026)
The genus Caenohalictus ranges from Mexico to southern South America and currently includes 65 valid names. Some species had their biology studied, indicating that Caenohalictus build nests in the soil and are solitary. A total of 10 species occur in Brazil, but the fauna has never been systematically studied. The objective of this work is to review the species present in southern Brazil, reevaluating known species and describing new species. We examined 627 specimens and recognized twelve species for the region: Caenohalictus curticeps (Vachal, 1903); C. implexus Moure, 1950; C. incertus (Schrottky, 1902); C. palumbes (Vachal, 1903); C. schulthessi (Vachal, 1903); C. tesselatus (Moure, 1940); and six new species: C. arcuatus sp. nov., C. cyanolucens sp. nov., C. leticiae sp. nov., C. longipalpis sp. nov., C. parviformis sp. nov., and C. sesquipalpis sp. nov. Caenohalictus mourei Almeida & Laroca, 2005 is considered to be a junior synonym of C. curticeps; Halictus (Paragapostemon) cicindulus Vachal, 1903 is considered to be a junior synonym of C. incertus. Males of C. implexus and C. palumbes were described for the first time. Identification key, 29 image plates, and distribution maps are presented.